Bioindicator Trends in Studying Environmental Pollution: A Systematic Review (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2025)
Scientists, government agencies, and the public are keenly interested in evaluating ecosystem health. As a result, there has been an increase in research investigating the efficacy of various bioindicators as markers of environmental pollutants. This article presents a review of bioindicators from 2013-2023 indexed by Scopus. The overall aim is to examine temporal trends in publications regarding bioindicators, contaminants of concern, species used as bioindicators, and potential future research. By entering the terms “bioindicators, environmental pollution, and environmental literature” into the search menu of the Scopus database, we obtained a total of 136 articles. After applying our criteria, we narrowed down our research to only 31 articles. We used the PRISMA framework for inclusion and exclusion purposes. Our SLR results showed that the most studied environmental pollution was air and freshwater pollution. The dominant keywords used in this study were bioindicators, animals, environmental monitoring, and biomonitoring. The most studied country for bioindicators of environmental pollution is Italy. The most studied types of pollution are heavy metal and chemical pollution. The most used bioindicator organisms are invertebrates and plants, while the least used are algae or diatoms. Future research on potential bioindicators includes the application of diatoms in water quality assessment, the relationship between bioindicator monitoring and its impact on communities, interspecies comparisons to identify the most effective indicators, and studies on the level of understanding and skills of communities in the use of bioindicator organisms. Overall, this review serves as a comprehensive reference for the development of research and application of bioindicators in environmental monitoring.